CTCF orchestrates the germinal centre transcriptional program and prevents premature plasma cell differentiation - Pérez-García, Arantxa; Marina-Zárate, Ester; Álvarez-Prado, Ángel F.; Ligos, Jose M.; Galjart, Niels; Ramiro, Almudena R. (Nature communications, 2017)
In germinal centres (GC) mature B cells undergo intense proliferation and immunoglobulin gene modification before they differentiate into memory B cells or long-lived plasma cells (PC). GC B-cell-to-PC transition involves a major transcriptional switch that promotes a halt in cell proliferation and the production of secreted immunoglobulins. Here we show that the CCCTC-binding factor (CTCF) is required for the GC reaction in vivo , whereas in vitro the requirement for CTCF is not universal and instead depends on the pathways used for B-cell activation. CTCF maintains the GC transcriptional programme, allows a high proliferation rate, and represses the expression of Blimp-1, the master regulator of PC differentiation. Restoration of Blimp-1 levels partially rescues the proliferation defect of CTCF-deficient B cells. Thus, our data reveal an essential function of CTCF in maintaining the GC transcriptional programme and preventing premature PC differentiation. Activated B cells differentiate into antibody-producing plasma cells in the germinal centre in secondary lymphoid organs. Here the authors show that this differentiation process and related transcription programs are modulated by the transcription factor CTCF, partly by suppressing the premature expression of Blimp-1.